Optimal strategies for correcting merotelic chromosome attachments in anaphase - Evgenii Kliuchnikov; Kenneth A. Marx; Valeri Barsegov; Alex Mogilner (Proceedings of the National Academy of Sciences, 2025)
Accurate chromosome segregation in mitosis depends on proper connections of sister chromatids, through microtubules, to the opposite poles of the early mitotic spindle. Transiently, many inaccurate connections are formed and rapidly corrected throughout the mitotic stages, but a small number of merotelic connections, in which a chromatid is connected to both spindle poles, remain lagging at the spindle’s equator in anaphase. Most of the lagging chromatids are eventually moved to one or the other pole, likely by a combination of microtubules’ turnover and the brute force of pulling by the microtubules’ majority from the one pole against the microtubules’ minority from the other pole. We use computer simulations from two stochastic models (1D and full 3D CellDynaMo model) combining force balances and microtubules’ dynamics for the lagging chromatids to investigate what maximizes the percentage of segregated laggards. We find that a) brute force tug-of-war with slow (< 0.0001 s −1 ) microtubules’ detachment rate can move asymmetric laggards to the poles in limited time, b) rapid (> 0.01 s −1 ) microtubules’ detachment rate leads to a significant loss of the laggards, and c) intermediate (~ 0.001 s −1 ) microtubules’ detachment rate ensures higher than 90% accuracy of segregation. The simulations also shed light on the waiting time required to correct the merotelic errors in anaphase and on the roles of chromatid-attached microtubule number and Aurora B–mediated, spatially graded regulation of microtubule kinetics in anaphase.